A controlled evaluation of social prescribing on loneliness for adults in Queensland: 8-week outcomes - Dingle, Genevieve A.; Sharman, Leah S.; Hayes, Shaun; Haslam, Catherine; Cruwys, Tegan; Jetten, Jolanda; Haslam, S. Alexander; McNamara, Niamh; Chua, David; Baker, James R.; Johnson, Tracey (Frontiers in Psychology, 2024)
There have been few controlled evaluations of Social Prescribing (SP), in which link workers support lonely individuals to engage with community-based social activities. This study reports early outcomes of a trial comparing General Practitioner treatment-as-usual (TAU) with TAU combined with Social Prescribing (SP) in adults experiencing loneliness in Queensland. Participants were 114 individuals who were non-randomly assigned to one of two conditions (SP, n = 63; TAU, n = 51) and assessed at baseline and 8 weeks, on primary outcomes (loneliness, well-being, health service use in past 2 months) and secondary outcomes (social anxiety, psychological distress, social trust). Retention was high (79.4%) in the SP condition. Time x condition interaction effects were found for loneliness and social trust, with improvement observed only in SP participants over the 8-week period. SP participants reported significant improvement on all other outcomes with small-to-moderate effect sizes (ULS-8 loneliness, wellbeing, psychological distress, social anxiety). However, interaction effects did not reach significance. Social prescribing effects were small to moderate at the 8-week follow up. Group based activities are available in communities across Australia, however, further research using well-matched control samples and longer-term follow ups are required to provide robust evidence to support a wider roll out.